INCLUDING FAMILY CAREGIVERS IN CANADIAN LONG TERM CARE: AMBIGUITY BETWEEN POLICY AND PRACTICE. (11th November 2018) - Keefe, J; Taylor, D; Parker, B; Tay, L; Cook, H
Abstract: Canada has one of the most policy-dense long-term care (LTC) systems in the world. These policies intend to frame best quality of care practices for people living in care. Unfortunately, the high volume of and gaps within policies create ambiguity for care providers in how to enact sometimes contradictory policy in keeping with the quality of end of life preferences of residents and their families. Our research team within SALTY (Seniors: Adding Life to Years) is assessing the complex interplay of LTC policies that influence quality of life (QOL) at end of life in LTC. We have analyzed more than 150 relevant policies from four Canadian provinces using a hermeneutics content analysis approach. Each document was categorized by specificity to LTC, and degree of compliance against a 6 level scale. Next, to assess the QOL elements, each policy was examined using Kane's (2006) 11 domains for measuring QOL. Findings were themed by applying a family-centred lens. Results demonstrate differences between each province's most binding compliance policy documents in terms of language, goal, intention, and context when considering friend/family caregiver involvement as a quality of end of life consideration. This presentation highlights the differences between four provinces located at the most eastern and western parts of the country. We highlight the implications of these policy differences against how persons living in care value family and friends as part of their quality of end of life experience.